Nearer the heart's desire : poets of the Rubaiyat : a dual biography of Omar Khayyam and Edward FitzGerald /: poets of the Rubaiyat : a dual biography of Omar Khayyam and Edward FitzGerald. (2016) - Richardson, Robert D, 1934-2020
No abstract available